Hubungan Fungsi Manajemen Kepala Ruangan dengan Kinerja Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit Jiwa Jambi - Mila Triana Sari; Miko Eka Putri; Daryanto Daryanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Nursing service management is an important aspect in moving nursing services towards good quality nursing services, accepted by patients as nursing service subjects. This research is a quantitative research with a cross sectional design. The population is all nurses in the Jambi Mental Hospital inpatient room as many as 113 people. Sampling using purposive sampling with a sample of 56 people. The results of the study showed that the results of statistical tests obtained P Value of 0.026. This shows that the function of the head of the room management is related to the performance of the implementing nurse. The conclusion is that there is a significant relationship between the management function of the head of the room and the performance of the nurses at the Jambi Mental Hospital.